(untitled) (Research, Society and Development, 2024)
Introduction: Tegumentary leishmaniasis is an infectious, non-contagious disease, caused by the protozoan of the genus Leishmania, characterized by vector transmission of the agent through wild reservoirs such as marsupials and other rodents or even domestic ones, such as dogs. Clinical symptoms mainly affect the skin and the lesion may be single or multiple with well-defined clinical aspects associated with involvement of the nasal mucous membranes with airway obstruction, epistaxis, ulcers, rhinorrhea, and oropharynx with odynophagia, hoarseness, and cough. Objectives: To report a case of rare cutaneous presentation of cutaneous leishmaniasis in pediatrics at the pediatrics service of Hospital Universitário Maria Aparecida Pedrossian (HUMAP). Methods: This case report is characterized by an observational, descriptive, and reflective study design. Clinical-laboratory information will be obtained through the medical record, after approval by the Research Ethics Committee Results: Female patient, 1 year and 2 months old, originally from Campo Grande (MS) with papule-like skin lesions that evolved into ulcers within 3 months. He used multiple treatments until a local biopsy was performed where the presence of Leishmania sp was identified, a treatment with Glucantime was started, and due to therapeutic failure, Liposomal Amphotericin was started. The patient continued treatment and outpatient follow-up, allowing regression and complete lesion healing. Conclusion: The epidemiological profile of Cutaneous Leishmaniasis still requires related studies that can analyze it in more depth, especially with regard to pediatric and adolescent patients.